A Musculoskeletal-Finite Element Study of Knee Joint Loading and Cartilage Mechanics in Children with Cerebral Palsy - Dongfei Huo; Run Lin; Junyan Li; Timothy P. Holsgrove; Dominic Farris; Dong Wang; Xijin Hua (Annals of Biomedical Engineering, 2026)
Purpose Cerebral palsy (CP) is typically associated with abnormal gait that may alter knee joint loading and accelerate joint degeneration. We developed an integrated musculoskeletal-finite element (MSK-FE) framework to quantify differences in knee joint biomechanics between children with CP and typically developing (TD) peers. Methods Gait data from 13 children (TD, n = 5; hemiplegia [HP], n = 4; diplegia [DP], n = 4) were analyzed using OpenSim to obtain knee kinematics and compressive knee joint reaction forces (KJRFs). These were applied to scaled 3D FE knee models, incorporating biphasic cartilage, menisci, and ligaments, at the first force peak, mid-stance, and second force peak to evaluate cartilage pressures. Results Compared with TD, both CP subtypes (HP and DP) exhibited greater knee flexion throughout the gait cycle, except for the affected limb in HP (HP A ), which showed reduced flexion during the stance phase. Peak KJRFs over the gait cycle were slightly higher in DP and HP A than in TD, whereas the unaffected limb in HP (HP UA ) generated the highest peak KJRFs among all groups, indicating compensatory overloading of the unaffected limb in HP. Correspondingly, FE analysis showed that peak cartilage contact pressures in the HP cohorts were significantly higher than in DP and TD, while pressures in DP were slightly higher than in TD over the gait cycle. The HP UA showed the highest contact pressures among all groups. Conclusion The MSK-FE framework quantified knee loading and cartilage contact pressure patterns in children with CP. These preliminary findings highlight subtype- and limb-specific gait-loading patterns and provide a mechanistic basis for future larger-scale and longitudinal investigations.